Case Report: Achieving ankle joint stability through early intervention in an 8-year-old with congenital fibular hemimelia - Yanhong Ma; Yanhong Ma; Na Pan; Na Pan; Gang Peng; Gang Peng; Rui Yang; Rui Yang (Frontiers in Pediatrics)
IntroductionCongenital Fibular Hemimelia (CFH), also known as congenital absence of the fibula, has an incidence of approximately 5.7–20 cases per million live births. Clinically, it manifests as partial or complete absence of the fibula, accompanied by tibial shortening and bowing, ball-and-socket or dish-shaped ankle joints, and tarsal anomalies. Surgical intervention serves as the primary therapeutic approach for CFH. Most pediatric patients require at least two surgical procedures, with the initial stage involving ankle reconstruction surgery to achieve joint stability, followed by subsequent limb lengthening procedures to correct limb length discrepancies between the lower extremities.Presentation of caseHere, we report for the first time a case of CFH with complete absence of fibula in a pediatric patient who achieved ankle stability through early application of splinting to maintain the right ankle in a functional position, thereby correcting valgus deformity and obviating the need for ankle reconstruction surgery. Following admission, the patient underwent limb lengthening surgery exclusive Ilizarov-based limb lengthening, achieving favorable clinical outcomes during early-to-mid postoperative follow-up.DiscussionCompared with the conventional “two-stage” surgical protocol for CFH, early conservative management demonstrates efficacy in correcting foot valgus deformity, thereby circumventing the need for multiple surgical interventions and associated morbidities in pediatric patients.ConclusionThis case report suggests that early conservative treatment may correct ankle instability in patients with CFH, thereby preventing the necessity for multiple complex surgical procedures. These findings highlight the critical importance of early screening and intervention, while providing novel insights into therapeutic paradigms for CFH management.